Carbon nanomaterials in clean energy hydrogen systems. - Zaginaichenko, S. Yu. (Svetlana Yu) (NATO science for peace and security. Series C, Environmental Security, 2011)
Workshop "Carbon Nanomaterials in Clean Energy Hydrogen Systems" held in June 2010. These original papers reflect recent progress in response to the modern-day requirements in chemistry of carbon nanomaterials and metal-hydrogen systems. Successor to the 2008 proceedings, this second volume focuses on research and application studies of materials capable of interacting actively with hydrogen, also addressing questions of hydrogen accumulation and storage. As a whole, it provides a review of the most relevant areas of hydrogen materials interactions and carbon nanomaterials science, making it invaluable for all researchers, physicists, chemists, post-graduates and young scientists interested in the structure, properties and applications of different nanocarbon material